(untitled) (Raparin Journal of Humanities (RJH), 2024)
The research study entitled (Linguistic Deviation in the Season of Farhad’s Rise by Anwar Qadir Mohammed According to Leach and Short Checklist). The field of the research is applied linguistics because linguistic deviation in stylistics is a field of applied linguistics. The data of the study is Anwar Qadir Mohammed’s poem (The Season of Farhad’s Rise). The research approach is analytic and practical which for linguistic deviation relies on the perspectives of Leech and Short’s checklist and for the quantities relies on the statistics. The study is important in the sense that it shows the style of the poetic language. The study consists of two sections, in addition to the introduction, conclusions and list of references. In the first section, entitled (Language of Poetry and Deviations), phonological, lexical, grammatical, dialectal, and linguistic, semantic, historical, register and graphological deviations are discussed. The second section entitled (The Relationship between semantic oddities, and deviant collocation and their Role in Poetry Interpretation) is discussed. In each poem, unusual, meaning, and collocational deviations are identified.